P042 Succinate promotes the conversion from white to beige adipose tissue in Crohn's Disease. (21st January 2022) - Montfort-Ferré, D; Menacho, M; Caro, A; Espina, B; Boronat-Toscano, A; Nuñez-Roa, C; Martí, M; Espin, E; Vendrell, J; Fernández-Veledo, S; Serena, C
Abstract: Background: Crohn's disease (CD) is characterized by severe transmural inflammation with subsequent destruction of the intestinal barrier. Bacterial infiltration across this leaky gut facilitates access to the mesenteric fat and the development of a subsequent inflammatory reaction in the surrounding adipose tissue named creeping fat (CF). Dysbiosis in CD patients has been associated with an increase in succinate-producing bacteria and a decrease in succinate-consuming bacteria. In fact, elevated succinate levels have been found in the intestine and feces of CD patients. Furthermore, succinate is an inductor of beige adipogenesis in white adipose tissue progenitors. Methods: Visceral and subcutaneous adipose tissue biopsies (VAT and SAT), serum, and plasma were obtained from a cohort of active CD (n=20), inactive CD (n=12), and control group (n=15). From adipose tissue biopsies, adipose-derived stem cells (ASCs) and adipose tissue macrophages (ATMs) were isolated. Different experiments were performed such as protein uncoupling protein 1 (UCP1)-immunohistochemistry and immunofluorescence, gene expression studies, adipose tissue explants, proteomic analysis of ASCs, succinate determinations, bio-impedancemetry, and infrared photographs. Results: Succinate treatment increased markers of beige adipose tissue in ASCs from controls and inactive CD patients (Fig. A). Surprisingly, the markers of beige adipose tissue were already high in ASCs isolated from active CD, due to being exposed to an environment with high levels of succinate in vivo . Proteomic analysis of isolated CD-ASCs revealed that these cells secrete beige adipose tissue-related proteins compared to Control-ASCs (Fig. B). Furthermore, bacterial translocation increases the conversion of pre-adipocytes from white to beige adipose tissue in CD individuals (Fig. C). Immunohistochemical study of UCP-1, confirms increased staining in adipose samples from CD patients from both depots (SAT and VAT) (Fig. D). Altogether, adipose tissue depots from CD patients had a conversion from white to beige adipose tissue with a high protein UCP1-gene expression. Thermic images show an increase of temperature in the intestinal area of active CD patients that is not observed in inactive CD patients or the control group. Conclusion: Understanding the role of beige adipose tissue in CD could help develop new therapeutic or diagnostic strategies in these patients.